The East Coast of Sumatra in the Spice Trade Network in the 19th Century - Syahrul Rahmat; Amin Suyitno; Endang Rochmiatun (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2023)
This article discusses the dynamics of the spice trade that occurred on the east coast of Sumatra, to be precise in the areas of Singapore and Palembang in the 19th century. The spice trade on the east coast of Sumatra in the 19th century was inseparable from the involvement of many nations in the spice commodity produced in the archipelago. In addition, this article also aims to analyze the impact of the spice trade on the formation of inter-ethnic networks. This study uses historical research methods, starting from heuristics, source criticism, interpretation and writing of history. Analysis of the results of research using the Islamic Maritime Civilization approach by K.N Chaudhuri and the Trade Network approach by J.C Van Leur, these two theories argue that maritime civilization is inseparable from the influence of agrarian civilization which has an impact on the formation of a network. The results of this study are; first, in the 19th century, Singapore and Palembang were areas that still existed as a place for the spice trade, and these two areas were not only a place for trade interactions, but also a spice producer. Second, the spice trade in this century has also formed networks between nations and ethnicities, such as local networks involving ethnic groups in Nusantara and international networks involving various ethnic groups and ethnic groups in the world.